Bonjour ,
A)
Suite arithmétique :
Un = Up + (n-p) × r
U12 = U5 + (12-5) × r
20 = 6 + 7r
7r = 20-6
7r = 14
r = 14/7
r = 2 .
U0 = U5 + (0-5) × 2
U0 = 6 + (-5) × 2
U0 = 6 - 10
U0 = -4 .
Donc :
Un = 2n-4 .
B)
Suite géométrique :
Un = Up × q^(n-p)
U3 = U1 × q^(3-1)
125 = 5 × q²
q² = 125/5
q² = 25
q =√25
q = -5 ou q = 5
On prend q = 5 (raison positive)
Le 1 terme :
vu que U1 est déjà mentionné dans l'énoncé au tant qu'un terme et non pas 1 terme , donc le 1 terme est U0 .
Donc :
U0 = U1 × 5^(0-1)
U0 = 5 × 0,2
U0 = 1 .
Un = 1 × 5^n
U n = 5^n .